2018
DOI: 10.1155/2018/9234105
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intervention Associated with Cognitive Improvement in Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease with the syndrome of cognitive and functional decline. Pharmacotherapy has always been in a dominant position for the treatment of AD. However, in most cases, drug therapy is accompanied with clinical delays when older adults have suffered from cognitive decline in episodic memory, working memory, and executive function. On the other hand, accumulating evidence suggests that exercise intervention may ameliorate the progression of cognitive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 110 publications
3
82
0
3
Order By: Relevance
“…We found performance in the object replacement task in 12-month-old APP/PS1 mice was improved by three months of voluntary wheel running, as compared to sedentary controls, while no improvements were detected in the novel object recognition task and Y-maze tasks. This inconsistency might be attributed to the small number of mice used in this pilot study, but this exercise-related improvement in performance on some memory-related tasks but not on others is consistent with similarly mixed impacts of exercise in previous studies of memory function in mouse models of AD [75] and in AD patients [81]. While a variety of brain regions are likely involved in each of these memory tasks, it has been shown that memory of an object's spatial location (evaluated with object https://doi.org/10.1371/journal.pone.0235691.g005…”
Section: Discussionsupporting
confidence: 82%
“…We found performance in the object replacement task in 12-month-old APP/PS1 mice was improved by three months of voluntary wheel running, as compared to sedentary controls, while no improvements were detected in the novel object recognition task and Y-maze tasks. This inconsistency might be attributed to the small number of mice used in this pilot study, but this exercise-related improvement in performance on some memory-related tasks but not on others is consistent with similarly mixed impacts of exercise in previous studies of memory function in mouse models of AD [75] and in AD patients [81]. While a variety of brain regions are likely involved in each of these memory tasks, it has been shown that memory of an object's spatial location (evaluated with object https://doi.org/10.1371/journal.pone.0235691.g005…”
Section: Discussionsupporting
confidence: 82%
“…We found performance in the object replacement task in 12-month-old APP/PS1 mice was markedly improved by three months of voluntary wheel running, as compared to sedentary controls, while no improvements were detected in the novel object recognition task and Y-maze tasks. This exercise-related improvement in performance on some memory-related tasks but not on others is consistent with similarly mixed impacts of exercise in previous studies of memory function in mouse models of AD [72] and in AD patients [78]. While a variety of brain regions are likely involved in each of these memory tasks, it has been shown that memory of an object’ s spatial location (evaluated with object replacement task) is highly dependent on hippocampal regions, while memory of an object’ s intrinsic characteristics (evaluated with novel object task) also involves significant contributions from other brain regions, such as the temporal lobe [79-81].…”
Section: Discussionsupporting
confidence: 90%
“…Recent and prior meta-analytic reviews [ 9 , 12 , 13 ] have found that numerous well-controlled studies have strengthened the claim that physical exercise can positively impact cognitive functioning in later life. Reviews continue to call for more well-controlled clinical trials to incorporate innovations that will reach and engage pre-clinical cases such as MCI where cognitive decline might go undetected yet harbor underlying neuropathology that could potentially be ameliorated with intervention [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%